2010
DOI: 10.1021/jm901851t
|View full text |Cite
|
Sign up to set email alerts
|

Development of Potent and Selective Inhibitors of ecto-5′-Nucleotidase Based on an Anthraquinone Scaffold

Abstract: ecto-5'-Nucleotidase (eN, CD73) plays a major role in controlling extracellular adenosine levels. eN inhibitors have potential as novel drugs, for example, for the treatment of cancer. In the present study, we synthesized and investigated a series of 55 anthraquinone derivatives as potential inhibitors of eN, 11 of which are novel compounds and another 11 of which had previously been described but have now been synthesized by an improved method. We identified several potent inhibitors of rat eN. The most poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
112
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 72 publications
1
112
0
1
Order By: Relevance
“…[16][17][18][19][20] However we do not believe that the BK channel agonist activity demonstrated here results from an interaction with purinoceptors or by inhibition of either eN or E-NTPDase, for a number of reasons. We have previously shown that suramin, [11] a non-specific purinoceptor antagonist and ecto-ATPase inhibitor has no effect on BK channels when applied (at concentrations up to 1 mM) to the cytosolic surface of BK channels in bladder smooth muscle.…”
Section: Structure Activity Relationship (Sar)mentioning
confidence: 71%
See 1 more Smart Citation
“…[16][17][18][19][20] However we do not believe that the BK channel agonist activity demonstrated here results from an interaction with purinoceptors or by inhibition of either eN or E-NTPDase, for a number of reasons. We have previously shown that suramin, [11] a non-specific purinoceptor antagonist and ecto-ATPase inhibitor has no effect on BK channels when applied (at concentrations up to 1 mM) to the cytosolic surface of BK channels in bladder smooth muscle.…”
Section: Structure Activity Relationship (Sar)mentioning
confidence: 71%
“…The effect of different substituents on the phenyl ring in the N 4 -position was investigated (see Table 1). Eight of the analogues (marked with an asterisk in Table 1) have been reported previously to act as purinoceptor antagonists, [16][17][18] ecto-5′-nucleotidease (eN) inhibitors, [19] or ectonucleoside triphosphate diphosphohydrolase (E-NTPDase) inhibitors, [20] but the remainder of the analogues were novel. When we examined the effects of these molecules on BK channels, we found that a significant number of the compounds were efficacious BK channel activators and shifted the activation V1/2 in excess of -80 mV (see Table 1).…”
mentioning
confidence: 99%
“…Moreover, we know that PKC stimulates AMP deaminase and 5' nucleotidase that both decrease AMP [10,11], which cancels the stimulation of AMP kinase and its inhibitory action on ACC, leading to an elevated synthesis of fatty acids and lipids in mitotic cells. It would thus be useful to inhibit PKC with non-toxic inhibitors, for example mastica the resin from pistacia lentiscus, [12] sphingosine [13] aloe vera anthraquinones such as emodin [14][15][16], there are many other inhibitors of PKC enzastaurin. Inhibiting PKC would also decrease the stimulation by PKC of AMP deaminase and 5'nucleotidase, and increase AMP.…”
Section: Counteracting the Metabolic Rewiring Of Tumor Cellsmentioning
confidence: 99%
“…Inhibiting PKC would also decrease the stimulation by PKC of AMP deaminase and 5'nucleotidase, and increase AMP. One may also inhibit AMP hydrolysis with anthraquinones or sulfonic acid derivatives [16,17]. The resulting increase of AMP kinase stimulated by AMP would inhibit ACC, and the fatty acid synthesis route, depriving mitotic cells from an essential membrane component [18].…”
Section: Counteracting the Metabolic Rewiring Of Tumor Cellsmentioning
confidence: 99%
“…药物的研究见诸报道 [14,15] . Figure 1 Structures of some anthraquinone derivatives 众所周知, 糖在生命系统中起着多种至关重要的作 用 [16] .…”
unclassified